Effect of Pesticides Application in Soils of Cardamom Hills in, Idukki, Kerala. - Susan Jacob and Dr. Resmi. G (International Journal of Engineering Research & Technology (IJERT), 2014)
An understanding of the effect of pesticides is essential for rational decision-taking regarding their authorization. The retention of a pesticide by soil can prevent its short-term access to ground or surface waters and its effects on non target organisms, but the persistence of the under graded pesticide or of harmful metabolites constitutes an ever present – and cumulative – risk to the environment and, eventually, to human health. The soil mineralogy, chemical decomposition and atmospheric conditions highly influence the pesticide retention and release of it and consequently the degradation of the compound. The analysis conducted on water samples across the entire district shows that the water sources are protected from contamination by any pesticides. However, the indiscriminate use of pesticides in Cardamom plantations will be a threat to the Indian Cardamom Hills, the Idukki District since the persistent pesticide residue of endosulfan, DDT and organophosphorous toxic chemicals are present in high concentration. The soil mineralogy of Idukki is favorable to its persistence and hence strict control and awareness to farmers for judicious use of pesticides is necessary to avoid pollution of water sources and contamination of the soil.